Diseño de una estación de carga mediante energía fotovoltaica para un sistema de electromovilidad náutica en el transporte de pasajeros en Cartagena - Porras Puello, Ramón; Sánchez Mc Nish, Jhon Alexander (Universidad Antonio Nariño, 2022)
This research project deals with the design of a charging station using photovoltaic energy for a nautical electromobility system for a future implementation in the transport of passengers to and from the islands near Cartagena, as a response to the environmental, economic problem, social and public policy that represents the use of internal combustion engines. Basically, it is proposed to design the motor-battery electric propulsion assembly for the type of boat commonly used and its respective charging station, based on photovoltaic energy.